2005
DOI: 10.1016/j.cmet.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional coactivator PGC-1α controls the energy state and contractile function of cardiac muscle

Abstract: Skeletal and cardiac muscle depend on high turnover of ATP made by mitochondria in order to contract efficiently. The transcriptional coactivator PGC-1alpha has been shown to function as a major regulator of mitochondrial biogenesis and respiration in both skeletal and cardiac muscle, but this has been based only on gain-of-function studies. Using genetic knockout mice, we show here that, while PGC-1alpha KO mice appear to retain normal mitochondrial volume in both muscle beds, expression of genes of oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
516
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 631 publications
(560 citation statements)
references
References 56 publications
34
516
1
9
Order By: Relevance
“…Earlier work had shown that hearts of mice lacking PGC-1␣ have reduced expression of many mitochondrial genes, a significant defect in ATP balance, and a blunted capacity to increase work output in response to an inotropic stimulus (26). However, the ability of hearts from mice mutant in PGC-1␣ to withstand a challenge in the form of pressure overload, such as seen in patients with hypertension or aortic stenosis, was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work had shown that hearts of mice lacking PGC-1␣ have reduced expression of many mitochondrial genes, a significant defect in ATP balance, and a blunted capacity to increase work output in response to an inotropic stimulus (26). However, the ability of hearts from mice mutant in PGC-1␣ to withstand a challenge in the form of pressure overload, such as seen in patients with hypertension or aortic stenosis, was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A number of gain-of-function assays have shown both in vitro and in vivo that PGC-1␣ activates most genes of mitochondrial biology and stimulates both fatty acid oxidation and oxidative respiration in cardiac tissue (22)(23)(24)(25). Conversely, we have recently shown that ablation of the PGC-1␣ gene caused important deficiencies in cardiac energy reserves and function (26). In the absence of PGC-1␣, the expression of mitochondrial genes in the heart was suppressed, the activities of mitochondrial enzymes were aberrant, and ATP production was blunted.…”
mentioning
confidence: 99%
“…The activities are most notable in highly metabolic tissues, such as brown adipose tissue, heart, skeletal muscle, liver and the CNS, where PGC-1a regulates the central characteristics of these differentiated tissues: thermogenesis, contractile force, oxidative fiber types, gluconeogenesis and beta-oxidation, and emerging roles in the CNS such as ROS adaptation and apoptosis. (Puigserver et al 1998;Herzig et al 2001;Lin et al 2002;Puigserver et al 2003;Rhee et al 2003;Arany et al 2005;St-Pierre et al 2006;Handschin et al 2007). While named for its interaction with PPARγ, many of these PGC-1-dependent adaptations appear to be largely dependent on ERRs and other metabolic transcription factors that are independent of PPAR/RXR Rhee et al 2003;Schilling et al 2006;Alaynick et al 2007;Huss et al 2007;Villena et al 2007).…”
Section: Pgc-1αmentioning
confidence: 99%
“…They interact with cardiomyocyte nuclear receptor factor‐1, estrogen related receptor‐α and peroxisome proliferator‐activated receptor‐α in increasing mitochondrial biogenesis 8. They also upregulate expression of nuclear and/or mitochondrial‐encoded mitochondrial proteins involved in fatty acid β‐oxidation, the tricarboxylic acid cycle and electron transport 9. PGC‐1 protein expression and the corresponding mitochondrial activity, is coordinated with several upstream stimuli reflecting the heart's energetic demand 10.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac phenotypes of mice lacking individual members of the PGC‐1 family are less severe. Pgc‐1 α deficient murine hearts show normal baseline contractile function but develop cardiac failure following increased afterload 9. Studies on Pgc ‐1β deficient hearts are more limited, but nevertheless report normal baseline cardiac function despite their reduced mitochondrial content, but blunted heart rate responses following adrenergic stimulation 14.…”
Section: Introductionmentioning
confidence: 99%